Consumers’ avoidance of information on red meat risks: information exposure effects on attitudes and perceived knowledge - Gaspar, R.; Luís, S.; Seibt, C.; Lima, M. L.; Marcu, A.; Rutsaert, P.; Fletcher, D.; Verbeke, W.; Barnett, J. (Journal of Risk Research, 2016)
In accordance with cognitive dissonance theory, individuals generally avoid information that is not consistent with their cognitions, to avoid psychological discomfort associated with tensions arising from contradictory beliefs. Information avoidance may thus make risk communication less successful. To address this, we presented information on red meat risks to red meat consumers. To explore information exposure effects, attitudes toward red meat and perceived knowledge of red meat risks were measured before, immediately after, and two weeks after exposure. We expected information avoidance of red meat risks to be: positively related to (1) study discontentment; and (2) positive attitudes toward red meat; and negatively related to (3) information seeking on red meat risks; and (4) systematic and heuristic processing of information. In addition, following exposure to the risk information, we expected that (5) individuals who scored high in avoidance of red meat risks information to change their attitudes and perceived risk knowledge less than individuals who scored low in avoidance. Results were in line with the first three expectations. Support for the fourth was partial insofar as this was only confirmed regarding systematic processing. The final prediction was not confirmed; individuals who scored high in avoidance decreased the positivity of their attitudes and increased their perceived knowledge in a similar fashion to those who scored low in avoidance. These changes stood over the two-week follow-up period. Results are discussed in accordance with cognitive dissonance theory, with the possible use of suppression strategies, and with the corresponding implications for risk communication practice.